Wild Horse Annie : friend of the mustangs - Fern, Tracey E. (Farrar Straus Giroux, 2019)
A picture book biography about activism, this is the story of Velma Johnston, a trailblazing woman who mobilized children in her crusade to save wild mustangs. Full color.